Factors that predict a positive response on gonadotropin-releasing hormone stimulation test for diagnosing central precocious puberty in girls - Junghwan Suh; Myung Hyun Choi; Ah Reum Kwon; Ye Jin Kim; Jin Woo Jeong; Jung Min Ahn; Hyun Wook Chae; Duk Hee Kim; Ho-Seong Kim (Korean Society of Pediatric Endocrinology, 2013)
PurposeThe rapid increase in the incidence of precocious puberty in Korea has clinical and social significance. Gonadotropin-releasing hormone (GnRH) stimulation test is required to diagnose central precocious puberty (CPP), however this test is expensive and time-consuming. This study aimed to identify factors that can predict a positive response to the GnRH stimulation test.MethodsClinical and laboratory parameters, including basal serum luteinizing hormone (LH), follicle-stimulating hormone (FSH), and estradiol (E2), were measured in 540 girls with clinical signs of CPP.ResultsTwo hundred twenty-nine of 540 girls with suspected CPP had a peak serum LH level higher than 5 IU/L (the CPP group). The CPP group had advanced bone age (P<0.001), accelerated yearly growth rate (P<0.001), increased basal levels of LH (P=0.02), FSH (P<0.001), E2 (P=0.001), and insulin-like growth factor-I levels (P<0.001) compared to the non-CPP group. In contrast, body weight (P<0.001) and body mass index (P<0.001) were lower in the CPP group. Although basal LH was significantly elevated in the CPP group compared to the non-CPP group, there was considerable overlap between the 2 groups. Cutoff values of basal LH (0.22 IU/L) detected CPP with 87.8% sensitivity and 20.9% specificity.ConclusionNo single parameter can predict a positive response on the GnRH stimulation test with both high sensitivity and specificity. Therefore, multiple factors should be considered in evaluation of sexual precocity when deciding the timing of the GnRH stimulation test.